Numerical study of using RDHDS connected PIP system to mitigate earthquake induced subsea pipeline vibrations - Bi, Kaiming; Hao, Hong (2017)
Pipe-In-Pipe (PIP) systems have been increasingly used in the subsea pipeline applications recently. By replacing the hard centralizers with the softer springs and dashpots to connect the inner and outer pipes, a PIP system can be considered as a structure-Tuned Mass Damper (TMD) system. It therefore has the potential to mitigate subsea pipeline vibrations when subjected to different vibration sources such as vortex shedding and/or earthquake excitations. This paper proposes using Rotational Friction Hinge Dampers with Springs (RFHDSs) to connect the inner and outer pipes. The Rotational Friction Hinge Dampers (RFHDs) are used to absorb the energy induced by the external vibration sources and the springs are used to provide the stiffness to the TMD system and to restore the original locations of the inner and outer pipes. To investigate the effectiveness of this new design concept, detailed three-dimensional (3D) Finite Element (FE) model of the RFHD is developed in ANSYS and the hysteretic behavior of RFHD is firstly studied. The calculated hysteretic loop is then applied to the 3D PIP FE model to estimate the seismic response. The effectiveness of the proposed system to mitigate earthquake induced vibrations is examined by comparing the seismic response of the proposed system with the traditional PIP system.